The German Long-Distance Bus Market — Returning to its Original Level in the Medium Term? - David Ennen; Janina Scheelhaase; Sven Maertens (Wirtschaftsdienst)
Abstract During the COVID-19 pandemic, long-distance bus transport in Germany came to an almost complete standstill. Since its liberalisation in 2013, long-distance bus transport has not only provided low-cost mobility, it has also contributed to income and employment in Germany. This article estimates the value added and employment created by the sector for the pre-COVID-19 year 2018. Our analysis suggests that the sector will reach pre-crisis levels relatively quickly as it mainly serves private travellers, especially VFR (visiting friends and relatives) travellers whose behavioural changes are less likely than those of business travellers.